2020
DOI: 10.1108/ijlma-07-2018-0145
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of labour exploitation: the case of Pakistan

Abstract: Purpose The issue of exploitative labour practices has been a persistent and recurring problem in the textile and garment industry. Despite increased media, policy and practitioners attention the evidence base remains unexplored. The International Labour Organization (ILO) has acknowledged the presence of labour exploitation in global supply chains because of private sectors’ employment practices. The purpose of this study is to apprehend views of multilevel stakeholders to explore the nature and driving mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The results further suggested that overall job satisfaction was pointedly higher among the satisfied respondents than that of the dissatisfied respondents. Several investigators, i.e., Asikullah [ 22 ]; Shan et al [ 73 ]; Syed and Mahmud [ 19 ]; Arslan [ 80 ]; Hechanova and Manaois [ 81 ]; Shi, Gordon and Tang [ 89 ] also found a significant impact of professional aspects on the overall job satisfaction of the respondents, which inveterate the outcomes of the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results further suggested that overall job satisfaction was pointedly higher among the satisfied respondents than that of the dissatisfied respondents. Several investigators, i.e., Asikullah [ 22 ]; Shan et al [ 73 ]; Syed and Mahmud [ 19 ]; Arslan [ 80 ]; Hechanova and Manaois [ 81 ]; Shi, Gordon and Tang [ 89 ] also found a significant impact of professional aspects on the overall job satisfaction of the respondents, which inveterate the outcomes of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…According to Hu et al [ 78 ] and Haleem et al [ 79 ], factors such as management chic, salary, working conditions, opportunities for training, performance reviews, and participation in decision-making have a big impact on how satisfied workers are with their jobs. Arslan [ 80 ] combines three types of exploitation—financial, physical, and psychological—that lead to labor unhappiness in Pakistan’s garment industry. According to Hechanova and Manaois [ 81 ], employee attitudes in the Philippines as well as organizational norms and controls are all influenced by ethical leadership that is subject to job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ideology of “living wage” in the garment industry has been a concern for International Labor Organization (ILO) for a long time and yet to date no major brand can validate that all the workers in their supply chain earn a living wage. Despite increased media, policy and practitioner's attention the evidence base remains unexplored the exploitation of human resources exists within the garment value chain (Cockbain et al , 2018; Arslan, 2020). The Clean Clothes Campaign in their research found that the workers' wages represent only a fraction of what consumers pay for the clothes because of deep-rooted structural power dynamics.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…As labor abuse is a common phenomenon experienced in the background of developing countries, my stance to use interpretative phenomenological approach (Arslan, 2020; Smith & Shinebourne, 2012) that creates a room to discuss the factors that influence the fishers’ mind rather than generate general theory.…”
Section: Methods and Methodologymentioning
confidence: 99%